Pengaplikasian Material Aluminium Composite Panel pada Perancangan Apartemen dan Soho di Kota Surabaya - rian ilham setiawan; suci ramadhani (Jurnal Lingkungan Karya Arsitektur (LingKAr), 2023)
The demand for residential space continues to increase with the amount of growth in a city. This is something that is experienced by large cities such as Surabaya. The demand for residential and office space for local residents and migrants is due to the increasing number of national and multinational companies operating in the city of Surabaya. The use of technology in the creation of building materials is one of the positive impacts that can be felt due to the rapid influence of modernization and globalization. The use of ACP material with a variety of materials and colors and ease of application in workmanship. Aluminum composite panel (ACP) building facade is a combination of aluminum panels and composite materials. This building material is made of polyethylene coated with aluminum panels on both sides. Aluminum composite panel itself is a rigid and sturdy sheet but with a relatively light weight. This building material is used to line the exterior or interior walls of the building. Because this material is available in metallic and non-metallic colors, it can add an artistic and luxurious impression to the building facade. The use of ACP material used on the facade of this building has various advantages such as variations in thickness, strength and brightness and attractive facade patterns.